What are the Needs of People Living in Remote Areas About the Essential Components of a Cardiac Rehabilitation Program? - Bernier, Jessica; Lavoie, Melissa; Poitras, Marie-Eve (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2021)
Introduction: Cardiac rehabilitation (CR) is an effective intervention to support patients in achieving their health objectives and in decreasing their risk of suffering from another myocardial infarction (MI). However, in several remote areas, no cardiac rehabilitation program (CRP) exists to support patients having experienced an MI. Before the creation of an intervention CRP adapted to patients living in these areas, it is essential to describe patients and healthcare professionals' needs regarding cardiac rehabilitation care. Objective: This study describes the needs of remote patients and healthcare professionals for the essential components in a CR program following myocardial infarction and percutaneous transluminal coronary angioplasty. Methods: A qualitative formative research study was conducted involving 10 men, 6 women, and 4 family physicians. Data were collected through in-depth individual interviews and one focus group. Results: Results show that patients who have suffered an MI have multiple unmet needs. This gap may be due to the variability in follow-ups by healthcare professionals. In the absence of a cardiac rehabilitation program, these patients must adapt quickly to their new health condition. Discussion and conclusion: It is critical that the needs of patients living in remote areas are better addressed in cardiac rehabilitation. To do this, it is essential to create a CRP that is tailored to the needs of both patients and professionals, thus providing patient-centered care.